Micropropagação de alcachofra a partir de plântulas germinadas in vitro - Didoné, Silvana Fátima (2013)
The artichoke Cynara cardunculus L. Var. scolymus Fiori is a herbaceous plant, outcrossing, belonging to the family Asteraceae, is a vegetable of high nutritional and medicinal value coming from the Mediterranean. The cultivation of the artichoke has limiting factors related to forms of sexual and vegetative propagation. Micropropagation is considered an alternative for obtaining homogeneous populations of good quality and free of disease. In order to establish protocol for micropropagation artichoke selected for fresh consumption, experiments were conducted to: (I) assess the ability of in vitro establishment from shoot tips obtained from adult plants grown in the field and seedlings obtained from seeds grown in the greenhouse, (II) to evaluate the possibility of establishing in vitro culture from explants obtained from seeds germinated in vitro, (III) evaluate the multiplication rate of selected progenies in different culture media, (IV) evaluate the percentage of rooting and acclimatized plants in different substrates. This study consisted of three experiments and was conducted in the Laboratory of Plant Biotechnology, and Department of Horticulture, the Passo UPF. In experiment I used apexes obtained from adult plants of three cultivars grown in the field to establish the micropropagation process. In experiment II Apical obtained from plants germinated in semi-protected environment six progenies artichoke were evaluated for the possibility of in vitro multiplication. In experiment III different explants obtained from seeds germinated in vitro three progenies ((P1) B2L4R6, (P2) and B1L4R7 (P3) B1L3R1) were evaluated for their potential in vitro multiplication using culture media (M1 and M2) and multiplied plantlets from shoot apex were rooted and acclimatized in three different substrates. In this experiment, the experimental design was completely randomized and the experimental unit consists of an apex / propagules / seedlings for stages of micropropagation and according to the availability of material. For statistical analysis, the data were subjected to analysis of variance with means compared by Tukey test at 5% probability of error. In experiment I and II, we found high levels of contamination by bacteria and fungi in the phase of isolation, even if used sodium hypochlorite and gentamicin in the culture medium. In the multiplication phase was also observed high rate of contamination of probable endogenous origin. In experiment III in vitro was established successfully without the presence of contaminants. However, only apexes were able to multiply in vitro. In the phase of proliferation was obtained at an average rate of multiplication varied between 6,4:1 and 2,09:1 between the two progeny used in four subcultures. The culture medium 1 (M1) was the most appropriate (1.0 mg.L-1 BAP and 0.1 mg L-1 NAA). The frequency of rooting is influenced by the progeny of which 51.9% of the progeny seedlings 1 (P1) rooted and only 14.9% of the progeny 2 (P2). The shoots without visible roots had higher survival during the acclimatization phase. The most suitable substrates for acclimatization in the two progenies evaluated was the substrate 1 (S1: Mecplant Horta 2 ®: 100%) and substrate 2 (S2: Mecplant Horta ® 2: 50% and Burnt rice husk: 50%). The survival rate at the end of acclimatization 75% for the substrate (S1). It was possible to establish the micropropagation process progenies selected for artichoke cultivation in vitro, using as source of explants seeds germinated in vitro